Tissue Factor as a Therapeutic Target - Key, Nigel S.; Bach, Ronald R. (Thrombosis and Haemostasis, 2001)
Tissue factor (TF) is a member of the cytokine receptor superfamily that functions as the essential receptor and co-factor for factor VII/ VIIa. Assembly of the TF-VII(a) complex on cellular surfaces initiates blood coagulation by limited proteolysis of zymogen factors IX and X, ultimately leading to the generation of thrombin. The realization that the TF pathway is the primary (if not the sole) mechanism for activation of coagulation in vivo has sparked an explosion in research in the last decade that has documented the central role of TF in certain forms of pathological thrombosis. Although these are too numerous to list, several are especially noteworthy by virtue of strongly supportive data in animal models. These include disseminated intravascular coagulation (DIC) induced by sepsis, and arterial thrombosis overlying an atherosclerotic plaque - the usual final event in myocardial infarction and unstable angina. In the case of arterial injury, inhibition of TF in animal models has also suggested that this pathway is important in mediating intimal hyperplasia. Other recent seminal observations include the recognition of several possible roles for TF that may not depend upon activation of the coagulation mechanism. For example, TF expression by certain tumor cell lines may determine enhanced metastatic potential, and in some tumors TF may promote angiogenesis (1).